TRAINING ON INTERACTIVE LEARNING STRATEGIES TO IMPROVE THE QUALITY OF THE TEACHING AND LEARNING PROCESS - Al Ayyubi, Ibnu Imam; Indrawan, Deni; Nurhikmah; Prayetno, Eko; Putra, Ari Limay Trisno (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
Training on interactive learning strategies for primary school teachers is an important step in improving the quality of the teaching and learning process. Many teachers still use conventional methods that are less effective in encouraging student engagement. This research focuses on the training provided to teachers of Sumur Bandung Private Primary School with the aim of improving their competence in implementing interactive learning strategies. The implementation method consists of three stages: problem identification, training, and mentoring. The results obtained show an increase in teachers' understanding and skills in utilising interactive learning media, particularly PowerPoint application, to create a more interesting and effective learning atmosphere. With this training, it is expected that the quality of learning at the primary school level can improve, so that students are more motivated and active in the learning process. It is expected to enhance the overall quality of education. Therefore, similar interactive learning strategy training should be conducted regularly to make lesson delivery more engaging and varied.